Accuracy and precision analyses of single-time-point dosimetry utilising physiologically-based pharmacokinetic modelling and non-linear mixed-effects modelling - Indra Budiansah; Deni Hardiansyah; Ade Riana; Supriyanto Ardjo Pawiro; Ambros J. Beer; Gerhard Glatting (EJNMMI Physics)
Abstract Purpose The aim of this study was to investigate the accuracy and precision of single-time-point (STP) dosimetry using a physiologically-based pharmacokinetic (PBPK) model with non-linear mixed-effects modelling (NLMEM). Methods Biokinetic data of [111In]In-DOTA-TATE in tumours, kidneys, liver, spleen, and whole body were collected from eight patients. The imaging was performed using planar scintigraphy at 2, 4, 24, 48, and 72 h after injection. Serum activity concentration was quantified at 5 and 15 min; 0.5, 1, 2, and 4 h; and 1, 2, and 3 d after injection. The PBPK model was fitted to the biokinetic data using NONMEM software version 7.5.1. Goodness-of-fit (GoF) criteria were visual inspection of the biokinetic curves, relative standard errors (RSEs) of the fitted parameters < 50%, and the absolute values of the off-diagonal elements in the correlation matrix < 0.8. All-time-point (ATP) fitting was performed, and the obtained absorbed doses (ADs) were used as reference (rADs). The leave-one-out Jackknife method was applied to calculate STP ADs (sADs). The accuracy of STP dosimetry was evaluated using the relative deviation between sADs and rADs. The time point, which resulted in the smallest root-mean-square error (RMSE), was selected as the optimal time point for STP dosimetry. The precision of the AD was calculated as ratio of AD RSE and AD values. Results The ATP fitting was adequate based on the GoF test. STP dosimetry at 48 h after injection provided an acceptable estimation of ADs, yielding the lowest RMSE values for the kidney and tumour, calculated as (7 ± 2)% and (14 ± 4)%, respectively. The ADs in STP dosimetry showed lower precision than in ATP dosimetry. For instance, the ADs precision in ATP and STP dosimetry for kidneys in term median[min, max] were 3[3, 3]% and 6[5, 6]%, respectively. Similar results were found for the tumours where the precision of the ADs in ATP and STP dosimetry were 4[4, 5]% and 9[8, 12] %, respectively. Conclusion STP dosimetry exhibits acceptable accuracy, although it shows a decrease in precision compared to ATP fitting. Precision information is clinically relevant for developing the optimal strategies for simplified dosimetry protocols.